2021
DOI: 10.5808/gi.20058
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study: nonsynonymous and synonymous substitution of SARS-CoV-2, SARS-CoV, and MERS-CoV genome

Abstract: The direction of evolution can estimate based on the variation among nonsynonymous to synonymous substitution. The simulative study investigated the nucleotide sequence of closely related strains of respiratory syndrome viruses, codon-by-codon with maximum likelihood analysis, z selection, and the divergence time. The simulated results, dN/dS > 1 signify that an entire substitution model tends towards the hypothesis's positive evolution. The effect of transition/transversion proportion, Z-test of selection, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…d) Ti/Tv ratio analysis: Lambda variant was found to have the lowest dN/dS ratio but the highest Ti/Tv ratio. A negative correlation has previously been observed between Ti/Tv ratio and dN/dS ratio under positive selection in the comparative analysis of SARS-CoV, SARS-CoV-2 and MERS-CoV for all the nucleotide substitution models (25). The reason for this could be explained by the fact that Tv substitutions favour dN.…”
Section: Omicron Genome Had Largest Number Of Mutations But Dn/ds Was...mentioning
confidence: 77%
See 1 more Smart Citation
“…d) Ti/Tv ratio analysis: Lambda variant was found to have the lowest dN/dS ratio but the highest Ti/Tv ratio. A negative correlation has previously been observed between Ti/Tv ratio and dN/dS ratio under positive selection in the comparative analysis of SARS-CoV, SARS-CoV-2 and MERS-CoV for all the nucleotide substitution models (25). The reason for this could be explained by the fact that Tv substitutions favour dN.…”
Section: Omicron Genome Had Largest Number Of Mutations But Dn/ds Was...mentioning
confidence: 77%
“…The ratio of dN/dS >1 indicates positive selection and has been reported in the S glycoprotein (22,23). Comparative analysis of SARS-CoV, SARS-CoV-2 and MERS-CoV substitution models showed a positive evolution model along with higher dN/dS, due to the dominance of dN (24,25). Studies of mutations in the diagnostic targets in COVID-19 have suggested that the N gene has the highest number of mutations (26,27).…”
Section: Introductionmentioning
confidence: 78%
“…Natural selection for immune evasion impedes the functionality of genes: SARS-CoV-2 has accumulated far more nonsynonymous mutations than synonymous mutations, indicating positive selection [65][66][67]. Amino acid substitutions presumably led to rapid diversification early in the pandemic as a result of the virus adapting to the new host species, and immune evasion has been a driving force since 2020 [68].…”
Section: Darwinian Mechanisms That Drive Degeneration Of Genetic Info...mentioning
confidence: 99%
“…The ratio of d N /d S > 1 indicates positive selection and has been reported in the S glycoprotein ( 22 , 23 ). Comparative analysis of SARS-CoV-2, SARS-CoV, and MERS-CoV showed a positive evolution model along with higher d N -d S due to the dominance of d N ( 24 ). Studies of mutations in the diagnostic targets in COVID-19 have suggested that the N gene has the highest number of mutations ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 97%